To simplify 2p + 7p, you first combine the like terms by adding the coefficients of the p variable. In this case, 2p + 7p is equal to 9p. Therefore, the simplified form of 2p + 7p is 9p.
7p + 2q = 46 . . . . (A) 5p + 3q = 36 . . . . (B) 3*(A): 21p + 6q = 138 2*(B): 10p + 6q = 72 Subtracting gives 11p = 66 so that p = 6 Substitute for p in (A): 7*6 + 2q = 46 or 42 + 2q = 46 which gives 2q = 4 so that q = 2 Solution: (p, q) = (6,2)
15 + 3 = 7p - 4p ie 18 = 3p so p = 6
A line with slope m has a perpendicular with slope m' such that:mm' = -1→ m' = -1/mThe line segment with endpoints (p, q) and (7p, 3q) has slope:slope = change in y / change in x→ m = (3q - q)/(7p - p) = 2q/6p = q/3p→ m' = -1/m = -1/(q/3p) = -3p/qThe perpendicular bisector goes through the midpoint of the line segment which is at the mean average of the endpoints:midpoint = ((p + 7p)/2, (q + 3q)/2) = (8p/2, 4q/2) = (4p, 2q)A line through a point (X, Y) with slope M has equation:y - Y = M(x - x)→ perpendicular bisector of line segment (p, q) to (7p, 3q) has equation:y - 2q = -3p/q(x - 4p)→ y = -3px/q + 12p² + 2q→ qy = 12p²q + 2q² - 3pxAnother Answer: qy =-3px +12p^2 +2q^2
It is: 11p+11 simplified
4p + 9 + (-7p) + 2 = 4p - 7p + 9 + 2 = -3p + 11
6nx + 7p - 14p + 2nx + 6x = 8nx - 7p + 6x
8p+5 = 11+7p= 8p-7p = 11-5p = 6
7+5q = -3 5q = -3-7 5q =-10 q = -2
7p+5q=-3, p=1 7Xp+5q=-3 7+5q=-3 5p=-10 p=-2
5p + 15p + 7p = 27p 5p - 15p + 7p = -3p 5p x 15p + 7p = 75p2 + 7p 5p/15p + 7p = 7p + 1/3
7p + 2 = 5p + 8 7p - 5p = 8 - 2 2p = 6 p = 3
14 + 6p = 6 + 7p 8 = p
4p+9-7p+2 -3p+11 p = 11/3
-7p + 5r - 6p + 3r = -7p - 6p + 5r + 3r = -(7 + 6)p + (5 + 3)r = -13p + 8r
4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11
Look at it this way: If p = 1, then 7p = 7. What plus 7 equals -3? Adding 7 to -10 would equal -3, so all we have to figure out is what times 5 would equal -10. 5 times -2 would equal -10 so q equals -2.